Exploring Collaborative Advantage: A Comprehensive Review and Synthesis of Research on Collaboration - Xiao, Qian; Zhuang, Winston Xiao (American Journal of Management, 2025)
The paper aimed to identify three influential factors that will impact collaborative performance. The first conceptualization of collaboration is discussed to illustrate the nature of collaboration. In the further examination, three factors of collaboration capability, timing of collaboration and relationship structure are discussed that, if manipulated well, contribute to collaborative advantage. In the end of the paper, implications of this research are discussed briefly.